Method for reducing residual stress of CVD zinc sulfide dome cover
Through separation and annealing treatment, the residual stress of the zinc sulfide ball cover is reduced, which solves the problem of deformation and cracking of the zinc sulfide ball cover during processing, and improves the processing pass rate.
Patent Information
- Application Number
- CN202411625825.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-07
AI Technical Summary
The zinc sulfide ball cover prepared by the CVD method has residual stress, which causes the material to be easily deformed or cracked during processing, reducing the utilization rate of the material.
The residual stress of the zinc sulfide ball cover is reduced by separating the ball cover, placing the ball cover on the buffer pad in the annealing furnace, cleaning the annealing furnace, injecting inert gas, annealing and controlling the pressure.
It effectively reduces the residual stress of the zinc sulfide ball cover, reduces the risk of deformation and cracking during the processing process, and improves the processing pass rate of the zinc sulfide ball cover.
Smart Images

Figure CN119571295A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of infrared optical material preparation, and more specifically to a method for reducing residual stress of a CVD zinc sulfide spherical cover. Background Art
[0002] Zinc sulfide (ZnS) is the only infrared optical material, except diamond, whose transmission band covers the entire band from visible light to long-wave infrared. It has strong spectral adaptability, high mechanical strength, good moisture resistance, and good thermal shock resistance. Its chemical properties are stable and its linear expansion coefficient is moderate, which is close to many metals or alloys.
[0003] At present, high-purity and high-performance zinc sulfide materials are mainly prepared by chemical vapor deposition (CVD) method, and the prepared zinc sulfide materials include flat blanks and special-shaped blanks (such as ball covers); after the zinc sulfide materials prepared by chemical vapor deposition are taken out of the furnace, residual stress remains inside the material; when the blanks are processed into products, due to the influence of residual stress, the materials are easily deformed or even cracked, which greatly reduces the utilization rate of the materials; especially for special-shaped materials, the internal residual stress is large, the release is slow, and the processing qualification rate is low, which has become a problem that needs to be solved urgently. Summary of the invention
[0004] In view of the problems existing in the background technology, an object of the present invention is to provide a method for reducing the residual stress of CVD zinc sulfide sphere cover, which can effectively reduce the residual stress of the zinc sulfide sphere cover product grown by the CVD method and after it is taken out of the furnace, and thus can effectively reduce the deformation problem of the processed zinc sulfide sphere cover, further avoid the risk of cracking of the processed zinc sulfide sphere cover, and greatly improve the qualified rate of zinc sulfide sphere cover processing.
[0005] Therefore, a method for reducing the residual stress of CVD zinc sulfide ball cover includes the following steps: S1, separating the ball cover: breaking the zinc sulfide ball cover product grown by CVD method and taken out of the furnace at the edges of the ball cover so that each ball cover is independent of each other; S2, placing the ball cover: placing the ball cover on the buffer pad on the layer plate in the annealing furnace, the buffer pad can withstand the annealing temperature of the annealing furnace, the ball cover opening faces the buffer pad, and there is no object pressing on the upper part of the ball cover; S3, cleaning the annealing furnace: closing the annealing furnace, using Use a vacuum pump to evacuate the annealing furnace to a pressure less than 10Pa, then stop evacuating the annealing furnace and fill it with inert gas. Wash the furnace for more than 5 times to replace the air in the furnace. Finally, perform a pressure holding test on the annealing furnace after evacuating the ultimate vacuum. When the pressure rise rate is less than 5Pa / h, the pressure holding is considered qualified. S4, introduce inert gas: continue to introduce inert gas, use a mass flow controller to control the inert gas flow rate to 1-20L / min, and the pressure in the annealing furnace is controlled at (1-5)×10 4Pa; S5, annealing: heat the annealing furnace to 800-1000°C at a heating rate of 0.1-1°C / min, and then keep it warm for 20-100h. After the insulation is completed, cool it to room temperature at a cooling rate of less than 1°C / min. In the process of introducing inert gas in step S4, after the temperature of the annealing furnace reaches the insulation stage, stop introducing inert gas and close the inert gas inlet and outlet valves; S6, control the pressure in the annealing furnace to normal pressure, and then take out the ball cover from the annealing furnace.
[0006] The beneficial effects of the present disclosure are as follows: in the method for reducing the residual stress of the CVD zinc sulfide sphere cover according to the present disclosure, through the operations of steps S1 to S4, as verified by the subsequent test process, the residual stress of the zinc sulfide sphere cover product grown by the CVD method and after being taken out of the furnace can be effectively reduced, thereby effectively reducing the problem of deformation of the processed zinc sulfide sphere cover, further avoiding the risk of cracking of the processed zinc sulfide sphere cover, and greatly improving the qualified rate of zinc sulfide sphere cover processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a schematic structural diagram of an annealing furnace in the method for reducing residual stress of a CVD zinc sulfide sphere cover according to the present disclosure.
[0008] Figure 2 A photo of the ball cover after processing in Example 1 at the time of completion of processing in the processing center is provided.
[0009] Figure 3 A schematic diagram of the method for characterizing residual stresses during testing is given. DETAILED DESCRIPTION
[0010] The accompanying drawings show embodiments of the present disclosure, and it will be understood that the disclosed embodiments are merely examples of the present disclosure, and the present disclosure can be implemented in various forms. Therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as the basis for the claims and as a representative basis for teaching ordinary technicians in the field to implement the present disclosure in various ways.
[0011] Reference Figure 1 According to the present disclosure, the method for reducing the residual stress of the CVD zinc sulfide sphere cover comprises the steps of:
[0012] S1, separating the spherical covers: separating the zinc sulfide spherical cover products grown by CVD method and taken out of the furnace at the edges of the spherical covers so that each spherical cover is independent of each other;
[0013] S2, placing the ball cover: placing the ball cover on the buffer pad on the layer plate in the annealing furnace, the buffer pad can withstand the annealing temperature of the annealing furnace, the opening of the ball cover faces the buffer pad, and there is no object pressing on the upper part of the ball cover;
[0014] S3, cleaning the annealing furnace: close the annealing furnace, use a vacuum pump to evacuate the annealing furnace, and reduce the pressure in the annealing furnace to less than 10Pa, then stop evacuating the annealing furnace, and fill the annealing furnace with inert gas, wash the furnace more than 5 times, and replace the air in the furnace; finally, perform a pressure holding test after the annealing furnace is evacuated to the limit, and when the pressure rise rate is less than 5Pa / h, it is considered that the pressure holding is qualified;
[0015] S4, introducing inert gas: Continue to introduce inert gas, use the mass flow controller to control the inert gas flow rate to 1-20L / min, and control the pressure in the annealing furnace to (1-5)×10 4 Pa;
[0016] S5, annealing: the annealing furnace is heated to 800-1000°C at a heating rate of 0.1-1°C / min, and then kept warm for 20-100h. After the end of the insulation, the temperature is cooled to room temperature at a cooling rate of less than 1°C / min. In the process of introducing inert gas in step S4, after the temperature of the annealing furnace reaches the insulation stage, the introduction of inert gas is stopped and the inert gas inlet and outlet valves are closed;
[0017] S6, controlling the pressure in the annealing furnace to normal pressure, and then taking out the ball cover from the annealing furnace.
[0018] In the method for reducing the residual stress of the CVD zinc sulfide sphere cover according to the present disclosure, through the operations of steps S1 to S4, as verified by the subsequent test process, the residual stress of the zinc sulfide sphere cover product grown by the CVD method and after being taken out of the furnace can be effectively reduced, thereby effectively reducing the deformation problem of the processed zinc sulfide sphere cover, further avoiding the problem of cracking of the processed zinc sulfide sphere cover, and greatly improving the qualified rate of zinc sulfide sphere cover processing.
[0019] In step S1, the CVD growth process is as follows: using a Zn-H2S reaction system, a ZnS spherical cover is grown in a chemical vapor deposition furnace, and the deposition device in the furnace mainly includes a crucible, a deposition chamber, and a discharge box, all of which are made of isostatic graphite material; the crucible is responsible for melting and evaporating the raw material solid zinc, the heating temperature is 560-660°C, and ZnS is grown in the deposition chamber; the deposition chamber is connected to the crucible through a partition with an internal gas path nozzle; the hydrogen sulfide gas and the melted and evaporated zinc vapor in the crucible are injected into the deposition chamber by the carrier gas argon through their respective gas paths to the nozzle , transferred to the surface of the graphite mold substrate for chemical reaction to generate ZnS; the heating temperature of the deposition chamber is 600-700℃, and the unreacted gaseous reactants, reaction byproduct hydrogen and the zinc sulfide particles that have not been effectively deposited will enter the discharge box with the carrier gas, and the gaseous substances will then enter the tail gas treatment system; after the reaction is completed, the introduction of hydrogen sulfide is stopped, the crucible heating is stopped, and the temperature is naturally reduced; the deposition chamber is cooled to 300℃ at a cooling rate of 0.5℃ / min, and the temperature is naturally reduced after 300℃; after the temperature in the furnace drops to room temperature, the ZnS ball cover is taken out of the furnace. The process of growing the zinc sulfide ball cover by CVD method in step S1 does not involve annealing itself, so annealing in the CVD deposition chamber can be avoided, the growth cycle of the CVD zinc sulfide ball cover can be shortened, and the production efficiency and output of the growth can be improved.
[0020] In step S1, each ball cover is independent of each other, so that each ball cover can be easily loaded into and taken out of the annealing furnace.
[0021] In step S1 , the total height of each spherical cover is 60-82 mm, and the wall thickness of the spherical cover is 10-20 mm.
[0022] In step S2, the cushion pad is but not limited to graphite paper. For example, the thickness of the graphite paper is 1-5 mm. Further, the thickness of the graphite paper is 2-5 mm. For example, the graphite paper has a carbon content greater than 99.5%, a sulfur content not higher than 200 PPM, a chlorine content not higher than 30 PPM, and a density deviation of ±0.5 g / cm 3 , tensile strength not less than 4.5 MPa, compression rate 35-45%, rebound rate not less than 9%, thermal weight loss at 450°C not more than 5%, stress relaxation rate not more than 10%. For example, graphite paper is purchased from Qingdao Jiuzhengyuan Graphite Technology Co., Ltd.
[0023] In step S2, the material of the layer plate is 310S stainless steel, and the thickness of the layer plate is not limited, as long as it can meet the strength requirements of the annealing furnace during operation and the space requirements for placing the ball cover. Figure 1In the example shown, the layer plates are set on the load-bearing bracket; the layer plates are spaced in multiple directions in the vertical direction, and the left and right ends of each layer plate are inserted into the grooves of the load-bearing bracket, and only one layer of ball cover is placed on each layer plate. The arrangement of multiple layer plates increases the number of ball covers processed by the annealing furnace. The arrangement of the grooves of the load-bearing bracket can flexibly adjust the intervals between adjacent layer plates in the vertical direction to adapt to the total height of different ball covers.
[0024] In step S3 and step S4, for example, the inert gas is nitrogen gas having a purity of not less than 5N.
[0025] In step S4, for example, the inert gas flow rate is 10 L / min, and the pressure in the annealing furnace is controlled at (2-4)×10 4 Pa.
[0026] In one example, in step S5, the temperature is increased to 800-950°C at a heating rate of 0.5-1°C / min, and then kept at this temperature for 20-30 hours. After the insulation is completed, the temperature is lowered to room temperature at a cooling rate of 0.2-0.5°C / min.
[0027] In one example, in step S6 , an inert gas is introduced to control the pressure in the annealing furnace to normal pressure.
[0028] [test]
[0029] Example 1
[0030] The method for reducing the residual stress of the CVD zinc sulfide sphere cover of Example 1 adopts the following steps:
[0031] S1, separating the spherical covers: the zinc sulfide spherical cover products grown by CVD method and taken out of the furnace are separated at the edges of the spherical covers so that each spherical cover is independent of each other, and the total height of each spherical cover is 60 mm, and the wall thickness of the spherical cover is 10 mm;
[0032] Among them, the CVD growth process is: using the Zn-H2S reaction system, growing the ZnS spherical cover in the chemical vapor deposition furnace, the deposition device in the furnace mainly includes a crucible, a deposition chamber, and a discharge box, all of which are made of isostatic graphite material; the crucible is responsible for melting and evaporating the raw material solid zinc, the heating temperature is 600℃, and ZnS grows in the deposition chamber; the deposition chamber and the crucible are connected by a partition with a gas path nozzle designed inside. The hydrogen sulfide gas and the melted and evaporated zinc vapor in the crucible are injected into the deposition chamber by the carrier gas argon through their respective gas paths to the nozzle, and are transmitted to the surface of the graphite mold substrate to undergo a chemical reaction to generate ZnS; the heating temperature of the deposition chamber is 660℃; the unreacted gas reactants, the reaction byproduct hydrogen, and the zinc sulfide particles that have not been effectively deposited will enter the discharge box with the carrier gas, and the gas substances will then enter the exhaust gas treatment system. After the reaction is finished, the introduction of hydrogen sulfide is stopped, the crucible heating is stopped, and the temperature is naturally reduced; the deposition chamber is cooled to 300°C at a cooling rate of 0.5°C / min, and the temperature is naturally reduced after 300°C; after the temperature in the furnace is reduced to room temperature, the ZnS spherical cover is taken out of the furnace;
[0033] S2, placing the ball cover: placing the ball cover on the cushion pad on the shelf in the annealing furnace, the cushion pad can withstand the annealing temperature of the annealing furnace, the opening of the ball cover faces the cushion pad, and there is no object pressing on the upper part of the ball cover, wherein the shelf is made of 310S stainless steel, the shelf is set on the load-bearing bracket, the shelf is spaced in multiple directions in the up and down directions, the left and right ends of each shelf are inserted into the corresponding grooves of the load-bearing bracket, only one layer of ball cover is placed on each shelf, the cushion pad is graphite paper, the graphite paper has a carbon content greater than 99.5%, a sulfur content not higher than 200PPM, a chlorine content not higher than 30PPM, and a density deviation of ±0.5g / cm 3 , tensile strength is not less than 4.5MPa, compression rate is 35-45%, rebound rate is not less than 9%, thermal weight loss at 450°C is not more than 5%, stress relaxation rate is not more than 10%, graphite paper is purchased from Qingdao Jiuzhengyuan Graphite Technology Co., Ltd., and the thickness of graphite paper is 2mm;
[0034] S3, cleaning the annealing furnace: close the annealing furnace, use a vacuum pump to evacuate the furnace, and reduce the pressure in the furnace to less than 10Pa, then stop evacuating the furnace, and fill the annealing furnace with inert gas, which is nitrogen with a purity of 5N. Wash the furnace more than 5 times to replace the air in the furnace; finally, perform a pressure holding test on the annealing furnace after evacuating the ultimate vacuum. When the pressure rise rate is less than 5Pa / h, it is considered to be qualified for pressure holding;
[0035] S4, introducing inert gas: continue to introduce inert gas, the inert gas is nitrogen with a purity of 5N, and the inert gas flow rate is controlled at 10L / min by a mass flow controller. The pressure in the annealing furnace is controlled at 2×10 4 Pa;
[0036] S5, annealing: the annealing furnace is heated to 800°C at a heating rate of 0.5°C / min, and then kept at this temperature for 30 hours. After the end of the heat preservation, the temperature is lowered to room temperature at a cooling rate of 0.2°C / min. After the temperature of the annealing furnace reaches the heat preservation stage, the inert gas is stopped from being introduced, and the inert gas inlet and outlet valves are closed;
[0037] S6, introducing an inert gas with a purity of 5N to control the pressure in the annealing furnace to normal pressure, and then taking out the ball cover from the annealing furnace.
[0038] Example 2
[0039] Except for the following differences, the rest is the same as Example 1:
[0040] In step S1, the total height of each ball cover is 76 mm, and the wall thickness of the ball cover is 15 mm;
[0041] In step S2, the thickness of the graphite paper is 5 mm;
[0042] In step S4, the pressure in the annealing furnace is controlled at 3×10 4 Pa;
[0043] In step S5, the temperature is raised to 900°C at a heating rate of 0.8°C / min, and then kept at this temperature for 30 hours. After the end of the heat preservation, the temperature is lowered to room temperature at a cooling rate of 0.3°C / min.
[0044] Example 3
[0045] Except for the following differences, the rest is the same as Example 1:
[0046] In step S1, the total height of each ball cover is 82 mm, and the wall thickness of the ball cover is 20 mm;
[0047] In step S2, the thickness of the graphite paper is 3 mm;
[0048] In step S4, the pressure in the annealing furnace is controlled at 4×10 4 Pa;
[0049] In step S5, the temperature is increased to 950°C at a heating rate of 0.8°C / min, and then kept at this temperature for 20 hours. After the insulation is completed, the temperature is lowered to room temperature at a cooling rate of 0.5°C / min.
[0050] Comparative Example 1
[0051] Only step S1 of embodiment 1 is adopted (ie, steps S2 to S6 of embodiment 1 are not executed).
[0052] Comparative Example 2
[0053] Only step S1 of embodiment 2 is adopted (ie, steps S2 to S6 of embodiment 2 are not executed).
[0054] Comparative Example 3
[0055] Only step S1 of embodiment 3 is adopted (ie, steps S2 to S6 of embodiment 3 are not executed).
[0056] The annealed ball covers of Examples 1-3 and the unannealed ball covers of Comparative Examples 1-3 were sent to a processing center for processing the inner and outer surfaces of the ball covers. Whether the ball covers were cracked during the processing was observed visually.
[0057] Figure 3 A schematic diagram of the method for characterizing residual stress during the test is given. The diameter of the ball cover is measured according to four equally divided lines A, B, C, and D, and the angle between adjacent diameter lines is 45°. After the ball cover is processed, the diameters of the four lines A, B, C, and D of the ball cover are measured at the time of completion of the ball cover processing. After the ball cover is left to stand for 3 days, the diameters of the four lines A, B, C, and D of the ball cover are tested again. The effect of the method for reducing the residual stress of the CVD zinc sulfide ball cover of Examples 1-3 and the influence of the residual stress of Comparative Examples 1-3 are verified by the change in the diameter of the ball cover.
[0058] The annealed ball covers of Examples 1-3 and the unannealed ball covers of Comparative Examples 1-3 did not crack during the machining process in the machining center. Figure 2 A photo of the ball cover after processing in Example 1 at the time of completion of processing in the processing center is provided.
[0059] Table 1 shows the results of the changes in the diameters of the spherical covers of Examples 1-3 after annealing and Comparative Examples 1-3 after the spherical covers were processed without annealing.
[0060]
[0061] As can be seen from Table 1, there is no change in the diameter difference of the spherical covers of Examples 1-3 after annealing at the time of completion of processing in the machining center and the diameter difference of the spherical covers taken out for testing again after standing for 3 days after completion of processing in the machining center; this indicates that the residual stress of the spherical covers of Examples 1-3 after annealing treatment by the method for reducing the residual stress of CVD zinc sulfide spherical covers is reduced to meet the requirements, and will not cause deformation problems of the zinc sulfide spherical covers after processing, thereby avoiding the risk of cracking of the processed zinc sulfide spherical covers.
[0062] As can be seen from Table 1, the difference between the diameter of the ball cover of Comparative Examples 1-3 that has not been annealed at the time of completion of processing in the machining center and the diameter of the ball cover that was taken out again for testing after being left to stand for 3 days after completion of processing in the machining center is large. This indicates that the residual stress of the ball cover of Comparative Examples 1-3 is large after not being annealed by the method for reducing the residual stress of the CVD zinc sulfide ball cover, causing the deformation problem of the zinc sulfide ball cover after processing, and then there is a risk of cracking of the processed zinc sulfide ball cover.
[0063] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for reducing residual stress of CVD zinc sulfide sphere cover, characterized in that: Includes steps: S1, separating the spherical covers: separating the zinc sulfide spherical cover products grown by CVD method and taken out of the furnace at the edges of the spherical covers so that each spherical cover is independent of each other; S2, placing the ball cover: placing the ball cover on the buffer pad on the layer plate in the annealing furnace, the buffer pad can withstand the annealing temperature of the annealing furnace, the opening of the ball cover faces the buffer pad, and there is no object pressing on the upper part of the ball cover; S3, cleaning the annealing furnace: close the annealing furnace, use a vacuum pump to evacuate the annealing furnace, and reduce the pressure in the annealing furnace to less than 10Pa, then stop evacuating the annealing furnace, and fill the annealing furnace with inert gas, wash the furnace more than 5 times, and replace the air in the furnace; finally, perform a pressure holding test after the annealing furnace is evacuated to the limit, and when the pressure rise rate is less than 5Pa / h, it is considered that the pressure holding is qualified; S4, introducing inert gas: Continue to introduce inert gas, use the mass flow controller to control the inert gas flow rate to 1-20L / min, and control the pressure in the annealing furnace to (1-5)×10 4 Pa; S5, annealing: the annealing furnace is heated to 800-1000°C at a heating rate of 0.1-1°C / min, and then kept warm for 20-100h. After the end of the insulation, the temperature is cooled to room temperature at a cooling rate of less than 1°C / min. In the process of introducing inert gas in step S4, after the temperature of the annealing furnace reaches the insulation stage, the introduction of inert gas is stopped and the inert gas inlet and outlet valves are closed; S6, controlling the pressure in the annealing furnace to normal pressure, and then taking out the ball cover from the annealing furnace.
2. The method for reducing residual stress of CVD zinc sulfide sphere cover according to claim 1, characterized in that: In step S1 , the total height of each spherical cover is 60-82 mm, and the wall thickness of the spherical cover is 10-20 mm.
3. The method for reducing residual stress of CVD zinc sulfide spherical cover according to claim 1, characterized in that: In step S1, the CVD growth process is: using a Zn-H2S reaction system, a ZnS spherical cover is grown in a chemical vapor deposition furnace, and the deposition device in the furnace mainly includes a crucible, a deposition chamber, and a discharge box, all of which are made of isostatic graphite material; the crucible is responsible for melting and evaporating the raw material solid zinc, the heating temperature is 560-660°C, and ZnS is grown in the deposition chamber; the deposition chamber and the crucible are connected by a partition with a gas path nozzle designed inside. The hydrogen sulfide gas and the melted and evaporated zinc vapor in the crucible are injected into the deposition chamber by the carrier gas argon through their respective gas paths to the nozzle, and are transmitted to the surface of the graphite mold substrate to undergo a chemical reaction to generate ZnS; the heating temperature of the deposition chamber is 600-700°C; the unreacted gas reactants, the reaction by-product hydrogen and the zinc sulfide particles that have not been effectively deposited will enter the discharge box with the carrier gas, and the gaseous substances will then enter the exhaust gas treatment system; after the reaction is completed, the introduction of hydrogen sulfide is stopped, the crucible heating is stopped, and the temperature is naturally reduced; the deposition chamber is cooled to 300°C at a cooling rate of 0.5°C / min, and the temperature is naturally reduced after 300°C; after the temperature in the furnace drops to room temperature, the ZnS ball cover is taken out of the furnace.
4. The method for reducing residual stress of CVD zinc sulfide spherical cover according to claim 1, characterized in that: In step S2, the buffer pad is graphite paper; and / or In step S2, the thickness of the graphite paper is 1-5 mm.
5. The method for reducing residual stress of CVD zinc sulfide spherical cover according to claim 4, characterized in that: In step S2, the graphite paper has a carbon content greater than 99.5%, a sulfur content not higher than 200 PPM, a chlorine content not higher than 30 PPM, and a density deviation of ±0.5 g / cm 3 , tensile strength is not less than 4.5MPa, compression rate is 35-45%, rebound rate is not less than 9%, thermal weight loss at 450℃ is not more than 5%, and stress relaxation rate is not more than 10%.
6. The method for reducing residual stress of CVD zinc sulfide sphere cover according to claim 1, characterized in that: In step S2, the material of the layer plate is 310S stainless steel.
7. The method for reducing residual stress of CVD zinc sulfide sphere cover according to claim 1, characterized in that: In step S2, the layer board is set on the load-bearing support; The layer plates are spaced apart in the up-and-down directions, and both ends of each layer plate in the left-and-right directions are inserted into the grooves of the load-bearing brackets, and only one layer of ball cover is placed on each layer plate.
8. The method for reducing residual stress of CVD zinc sulfide sphere cover according to claim 1, characterized in that: In step S4, the inert gas flow rate is 10 L / min, and the pressure in the annealing furnace is controlled at (2-4)×10 4 Pa; and / or In step S3 and step S4, the inert gas is nitrogen with a purity of not less than 5N.
9. The method for reducing residual stress of CVD zinc sulfide sphere cover according to claim 1, characterized in that: In step S5, the temperature is raised to 800-950°C at a heating rate of 0.5-1°C / min, and then kept warm for 20-30 hours. After the insulation is completed, the temperature is lowered to room temperature at a cooling rate of 0.2-0.5°C / min.
10. The method for reducing residual stress of CVD zinc sulfide dome according to claim 1, characterized in that: In step S6, an inert gas is introduced to control the pressure in the annealing furnace to normal pressure.
Citation Information
Patent Citations
Method for annealing CVD-ZnS crystal material
CN103938274A
Annealing equipment and process for multi-spectral zinc sulfide window
CN110923676A
Method for preparing infrared composite material and vacuum chemical vapor deposition furnace
CN112853312A
Method for reducing internal stress of multispectral zinc sulfide
CN115784773A
Device for preparing high optic uniformity CVDZnS ball cover
CN200988773Y